The Effect of Professional and Non-Professional Courses on Mental Health among College Students - Pant, Naveen; Sharma, Om Kant (Islamic Guidance and Counseling Journal, 2021)
This study is designed to examine the impact of types of courses of study (professional/non-professional courses) on Mental Health (Anxiety, Depression, Loss of behavior or Emotional control, General positive affect, Emotional ties, or Life satisfaction) among postgraduate students. The sample is comprised of both professional and non-professional courses students of Gurukula Kangri Vishwavidyalaya, Haridwar, India. The purposive non-probability sampling method is used to select the sample of the study. The Mental Health Inventory (MHI-38) and interviews have been conducted to find out the level of mental health and its subscales among college students. As a result of the study, mental health subscales of Depression, Loss of Behavior or Emotional control, General positive affect, Emotional ties turned out to be significant functions of mental health among students, wherein these four subscales non-professional courses students found to be significantly higher than the students of the professional course. Further anxiety and life satisfaction turned out a not significant function of mental health among professional and non-professional course students.